2010
DOI: 10.1002/mds.23322
|View full text |Cite
|
Sign up to set email alerts
|

Metric properties of the mini‐mental Parkinson and SCOPA‐COG scales for rating cognitive deterioration in Parkinson's disease

Abstract: The SCOPA-COG has some advantages over the MMP, the most important being a greater discriminative ability. Multilevel hierarchical analysis clarified the necessity of stratifying the PD population according to educational background, years of illness, and H&Y stage when using these scales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 43 publications
4
12
0
Order By: Relevance
“…In agreement with previous literature (Carod-Artal et al, 2008;Marinus et al, 2003;Serrano-Duenas et al, 2010;Verbaan et al, 2007), we showed that the SCOPA-Cog was able to accurately represent the heterogeneous composition of our neurologically and cognitively mixed study population. Indeed, the scores obtained by our patients covered almost the entire score range of the scale, the distribution was virtually symmetric, the average score overlapped with the median, and there was no ceiling or floor effect.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In agreement with previous literature (Carod-Artal et al, 2008;Marinus et al, 2003;Serrano-Duenas et al, 2010;Verbaan et al, 2007), we showed that the SCOPA-Cog was able to accurately represent the heterogeneous composition of our neurologically and cognitively mixed study population. Indeed, the scores obtained by our patients covered almost the entire score range of the scale, the distribution was virtually symmetric, the average score overlapped with the median, and there was no ceiling or floor effect.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study we also confirmed previous evidence about the goodness of the instrument's structure (Carod-Artal et al, 2008;Marinus et al, 2003;Serrano-Duenas et al, 2010), as all the subtests appeared to be tapping the same general cognitive construct, each one being necessary for the consistency of the scale. Precision analysis yielded less satisfying results, indicating that the difference between true cognitive level and observed SCOPA-Cog scores may be relatively large.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations